The gathering ebook - Armstrong, Kelley (Darkness Rising, 2011)
Strange things are happening in Maya's tiny Vancouver Island town. First, her friend Serena, the captain of the swim team, drowns mysteriously in the middle of a calm lake. Then, one year later, mountain lions are spotted rather frequently around Maya's home—and her reactions to them are somewhat . . . unexpected. Her best friend, Daniel, has also been experiencing unexplainable premonitions about certain people and situations. It doesn't help that the new bad boy in town, Rafe, has a dangerous secret, and he's interested in one special part of Maya's anatomy—her paw-print birthmark.